2002
DOI: 10.1116/1.1529654
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of various copper seed layers for copper electrodeposition applicable to ultralarge-scale integration interconnection

Abstract: As a superior substituent for the chemical-vapor deposition and physical-vapor deposition ͑PVD͒ Cu processes in an ultralarge-scale integrated interconnection, electrodeposition on two kinds of electroless-plated Cu seed layers was investigated. Co͑II͒ and formaldehyde were used as reducing agents for each electroless plating. Two samples of electroless-plated seed layers had relatively higher resistivity due to rough and irregular grains and weakly developed ͑111͒ texture, which are peculiarities of electrole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Direct-write tools (e.g. scanning beam and scanning probe systems) exhibit the flexibility of softwarereconfigurable instruments, but they are generally slow, which limits manufacturing throughput and increases production costs [5][6][7][8][9][10][11][12]. Soft lithography is an inexpensive method suitable for combining 'top-down' patterning with 'bottom-up' molecular self-assembly [5][6][7][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Direct-write tools (e.g. scanning beam and scanning probe systems) exhibit the flexibility of softwarereconfigurable instruments, but they are generally slow, which limits manufacturing throughput and increases production costs [5][6][7][8][9][10][11][12]. Soft lithography is an inexpensive method suitable for combining 'top-down' patterning with 'bottom-up' molecular self-assembly [5][6][7][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Electroless deposition involves chemical instead of electrochemical reduction, and thus can be applied to substrates covered by electrically insulating oxide layers, enabling applications to base metals and interconnect diffusion barriers. 1,2 Galvanic displacement, a type of electroless deposition in which the substrate or an adsorbed species acts as the reducing agent, can produce nanometer-thickness films on semiconductors and noble metals. 3,4 Galvanic deposition of copper layers has been reported on oxide-covered materials such as aluminum, tantalum, as well as TiN and TaN diffusion barriers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Then the Cu deposited substrates were annealed at 120 °C for 3 h. The annealing process after the deposition of Cu is known to promote interlayer mixing at the interface between deposited Cu and the substrate and stabilize the interface. 32,33 Previous observation indicated that the promoted interlayer mixing by the annealing process induced the decrease in residual stress and thus caused an increase in the adhesion between the substrate and Cu film. 34 However, the annealing temperature was low enough to avoid the surface oxidation of Cu, as was confirmed by the X-ray diffraction patterns (see Figure S1 of the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%